Setting boundaries at work: Development and validation of the Sexual Identity Disclosure Dynamics Scale - Corlett, S.; Di Marco, D.; Hoel, H.; Munduate, L.; Arenas, A. (Psychology of Sexual Orientation and Gender Diversity, 2024)
This study describes the development and validation of the Sexual Identity Disclosure Dynamics Scale (SIDDS), a new measure to assess the process of disclosure at work that includes the reaction of supervisors, coworkers, and clients to the disclosure preferences of lesbian, gay, and bisexual (LGB) employees. The items were constructed based on the results of a previous study on sexual identity management at work drawing on boundary theory. An exploratory factor analysis (EFA) with a sample of n = 285 LGB employees showed that the items of the SIDDS load into a four-factor solution: integration, segmentation, intrusion violation, and distance violation. A confirmatory factor analysis (CFA) showed that the preliminary model had an acceptable model fit to the data in an independent sample of n = 458 LGB employees. Data offered evidence of acceptable reliability in both samples (? = .75–.95), and measurement invariance was established between sexual and gender identities and between countries in which most of the participants were working. The developed scale correlated with measures that assess authenticity at work, climate of inclusion, segmentation preferences and supplies at work, and sexual identity management strategies, showing evidence of convergent and concurrent validity. Discriminant validity was established with the SIDDS being unrelated to task variety. The SIDDS can be used to understand how the reaction of the audience to sexual identity disclosure preferences impacts on the health, attitudes, and performance of LGB employees. Limitations and suggestions for future research are discussed.